2015
DOI: 10.1055/s-0040-1703908
|View full text |Cite
|
Sign up to set email alerts
|

KAP study of solid waste disposal of households in Kuttar & Manjanadi Panchayath covered under gramaskhema programme of K.S. Hegde Medical Academy

Abstract: An important problem faced by many societies across the world is unhealthy disposal of solid wastes. Knowledge, attitude, practices of people plays a crucial role as their view point is extremely vital in providing solutions to future environmental problems. A cross sectional study was conducted among the households of Kuttar and Manjanadi villages and a sample of 120 households were studied. Majority had a good knowledge about the ill effects of improper solid waste disposal and that 82.5% said collectively t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
2
13
1
Order By: Relevance
“…• Results obtained from this study consistent to the results reported in another study conducted by Arora L et al it was found that 162(54%) of the respondents could be classified as possessing low knowledge, whilst 138(46%) respondents were having medium level of knowledge regarding waste management (2).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…• Results obtained from this study consistent to the results reported in another study conducted by Arora L et al it was found that 162(54%) of the respondents could be classified as possessing low knowledge, whilst 138(46%) respondents were having medium level of knowledge regarding waste management (2).…”
Section: Discussionsupporting
confidence: 89%
“…Waste is a material that no longer serves a purpose and so is thrown away (1) . In somecases what one person discards may be re-used by someone else (2) . All wastes are particularly hazardous (3) .…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted in India, to assess the knowledge, attitude and practices towards waste disposal in cities and towns generated an estimated 6 million tones of household waste, and it was about 484 million tones. More than 25% of the waste is not collected at all 70% of the Indian cities lack adequate capacity to transport it and there are no sanitary for landfills to dispose of the waste (Kiran et al, 2015). Study was conducted in Somalia to assess the practices of people regarding household waste disposal, most of people 62% waste the garbage nearby their houses in open places.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ways that individuals are aware of, think of, and behave toward SWM would be the key to solving environmental problems (Kiran et al, 2015). It is necessary to disclose the determinants of the communities’ knowledge, attitudes, and practices (KAP).…”
Section: Introductionmentioning
confidence: 99%